EVALUATION OF THE PAVEMENT ROUGHNESS OF AMIR TEMUR STREET IN TASHKENT - Isayev Jahangir Azamat oʻg‘li (Bright Mind Publishing, 2025)
This article presents the development of recommendations based on the results of an assessment of the transport and operational condition of city streets.
Keywords: Pavement, surface course roughness, 3 - meter straightedge, Amir Temur Street.